Ḥūr and Qur’anic Beauty beyond Patriarchal Dualism in a Khalīfah–Mīzān Reading - Habil Abyad; Intihaul Fudola; Arif Al Anang; Yolan Hardika Pratama (UIN Sunan Kalijaga Yogyakarta, 2026)
Despite extensive debates on ḥūr in Qur’anic exegesis, the imagery of paradise is still frequently read through patriarchal assumptions that reduce female figures to sensual reward and obscure the Qur’an’s ethical and ecological horizon. This article aims to critique patriarchal readings of ḥūr as feminized paradisiacal reward and to propose a khalīfah–mīzān-guided eco-tafsīr that reorients Qur’anic “beauty” toward gender and ecological justice. The study uses qualitative, text-based research through comparative hermeneutical tafsīr analysis of Qur’anic passages on ḥūr and related ethical principles (khalīfah and mīzān), employing lexical–semantic analysis, close reading, and cross-tafsīr comparison. The findings show that patriarchal interpretations are sustained by an androcentric dualism that separates humans from nature and legitimizes domination, whereas a khalīfah–mīzān framework enables a relational reading that affirms women’s subjectivity and shifts beauty away from commodification toward ecological intimacy. Overall, this approach offers a text-grounded pathway for reading paradise imagery as an ethical horizon that integrates gender justice with ecological responsibility.